2015
DOI: 10.1063/1.4936572
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive assessment of maximum power point tracking techniques under uniform and non-uniform irradiance and its impact on photovoltaic systems: A review

Abstract: Under shading condition, the power–voltage characteristics of the photovoltaic (PV) modules exhibit complexity with multiple numbers of peaks. Existence of multiple peaks leads to additional difficulties in tracking maximum power point (MPP) and shall mar efficiency of PV arrays under shading, if appropriate measures are not taken. It is due to the nonlinear characteristics of PV cell, maximum power can be extracted under particular weather condition. Maximum power point tracking (MPPT) techniques are used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 102 publications
0
20
0
Order By: Relevance
“…The HC operational methodology is outlined in Table 3, where the fixed δ step size may be used, but this does not guarantee a fixed voltage change [31], [32]. Furthermore, the conventional HC method fails to track the MPP effectively under intermittent weather conditions because of a steady duty cycle [15].…”
Section: ) Hill Climbing (Hc) Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HC operational methodology is outlined in Table 3, where the fixed δ step size may be used, but this does not guarantee a fixed voltage change [31], [32]. Furthermore, the conventional HC method fails to track the MPP effectively under intermittent weather conditions because of a steady duty cycle [15].…”
Section: ) Hill Climbing (Hc) Methodsmentioning
confidence: 99%
“…In addition to this, Salam et all in [14] have identified soft computing MPPT techniques as a possible option. However, a minimal number of reviews [9], [15] discussed on MPPT under uniform solar irradiance and PSC conditions. "Google Scholar" survey for last five years was conducted from 2015 to 2020 to investigate how many review article has been published on "Maximum Power Point Tracking" and "Maximum Power Point Tracking Under Uniform Solar Irradiations", "Under Non-Uniform Solar Irradiation" and "Hybrid Optimization MPPT" On the first search on Maximum Power Point Tracking, we found seventy-one review articles when the search was specified and narrowed to "Uniform Solar Irradiations" four review papers, on "Non-Uniform Solar Irradiation" seven and on "Hybrid Optimization MPPT" no review articles were found.…”
Section: Introductionmentioning
confidence: 99%
“…9 To obtain the MPP, various techniques such as perturb and observe (P&O), incremental and conductance (I&C), fuzzy logic (FL), neural network (NN), and sliding mode control are illustrated in the literature. [10][11][12][13] P&O and I&C are unable to tackle deviations of MPP due to varying climatic changes and are dependent on the perturbation step size. Genetic algorithm-based MPPT is unable to find the optimal point satisfactorily under fluctuating weather conditions.…”
Section: Motivationmentioning
confidence: 99%
“…A low-pass filter is used to clear the DC components. The d and q-axes currents consist of fundamental and harmonic segments as in Equation (10) and (11) as follows:…”
Section: : ð9þmentioning
confidence: 99%
See 1 more Smart Citation